Legality of Reserve Components in Indonesia in State Defense Efforts, From an International Law Perspective - Pattikawa, George Norman Collin; Laturette, Adonia Ivone; Akyuwen, Rory Jeff; Wattimena, Josina Augustina Yvonne (Journal of Ecohumanism, 2025)
The formation of a reserve component in state defense efforts is questionable the legality because it directly contradicts the provisions of international law, especially the principle of distinction. This is evidenced by the fact that the formation of reserve components in state defense efforts creates uncertainty about the legal status of the civilian population involved. Starting from that, the problem studied here is including the conflict between the two legal systems, namely international law and national law. This paper is divided into several sections of discussion, including: First, it examines the concept of state defense in terms of its practical ontology. Second, it looks at the clash between the international and national legal systems. Third, mapping the impact of the problem. Finally, it offers relevant solutions that can be applied to overcome the problems that occur. The conclusion that can be drawn from this discussion is that the formation of reserve components in state defense efforts is declared illegal because it is contrary to international law and has the potential to result in human rights violations. Therefore, to be able to anticipate these implications, the right to refuse military service and the principle of alternative duty must be accommodated.